Cross-Country Unemployment Insurance, Transfers, and Trade-Offs in International Risk Sharing - Zeno Enders; David A. Vespermann (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We assess to which degree an international transfer mechanism can enhance consumption risk sharing as well as allocative efficiency and apply our results to the implicit transfers generated by a potential European unemployment benefit scheme (EUBS). Specifically, we first develop a simple model with nominal rigidities to build intuition by deriving analytical results. We then use a rich DSGE model, calibrated to the Core and the Periphery of the euro area, to quantitatively analyze the changing dynamics that a EUBS brings about. We find that a EUBS can provide risk sharing by stabilizing relative consumption as well as unemployment differentials. Following supply shocks, however, the cross-country transfer embodied in the unemployment benefits is spent to a large degree on relatively inefficiently produced goods in the receiving countries. This renders the allocation even more inefficient by opening country-specific labor wedges further, also after government-spending shocks. Yet, since this trade-off between allocative efficiency and consumption risk sharing does not exist after certain demand shocks, the welfare effects of a EUBS depend on the cause for international unemployment differentials. A EUBS that is only active after specific shocks would therefore maximize overall welfare. Even without this feature, a EUBS would raise Core's welfare in the quantitative model, leaving Periphery's welfare almost unchanged.
Keywords: F45; F44; E32; 330; cross-country transfers; international unemployment insurance; EMU European business cycles; optimum currency area; structural reforms